IDENTIFICATION OF HUMAN BEHAVIOR IN VISUAL CROWD SCENE USING SPACE-TIME FEATURES AND 3D-SCALE CONVOLUTIONAL NEURAL NETWORK APPROACHES - SHUAIBU, ALIYU NUHU (2018)
Human behavior analysis has become a critical area of research in computer vision and artificial intelligence research community. In recent years, the conventional video surveillance systems of crowd scenes have witnessed an increased demand in different applications such as safety, security, entertainment and personal archiving.